A força mobilizadora do binômio sujeito-lugar na patrimonialização proativa - Koffer, Amanda Lovatti Coelho (2024)
Assuming territorial heritage as a complex process, the result of a series of relationships established between physical elements and structuring rules of the territory, it is understood the need to review current strategies for its recognition and operation, as these tend to be understood as it as an inert artifact, disconnected from territorial processes. Therefore, it is considered necessary that the inhabitant, an agent immersed in territorial dynamics, assume the leading role in the operation of territorial heritage. Thus, the aim of this work is to contribute to the discussion and methodological development for the valorization of territorial heritage, based on concepts referring to proactive patrimonialization, disconnected from institutions, through the actions of a projecting community. To this end, the methodological approach of the Italian Territorialist School – ETI is adopted, articulating and expanding conceptual and practical understandings in a transdisciplinary way, between architecture, philosophy and geography. Under a qualitative and descriptive approach, the research methodology is characterized by experimental and participatory actions. The activities linked to the methodological approach intend to analyze proactive patrimonialization as a theoretical and practical procedural conception, develop and experiment a proposal for interaction with a community context in order to identify local processes, considering the values of identity, resource and territorial capital. The interaction is anchored in participant observation, in which the researcher positions himself as an observer of a local reality, in order to investigate it through a direct relationship with the interlocutors, understanding the context of the research and collecting the necessary data to identify attributes that refer to actions linked to the proactive patrimonialization process. In this sense, the work aims to achieve a new interpretation regarding the way of acting on the territory as heritage, contributing to the understanding that the force that moves patrimonialization comes from the subject-place link and the local community project in which it is inserted, through the mobilization of inhabitants around a common objective